2010
DOI: 10.1016/j.trstmh.2009.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and low birthweight in western Sudan

Abstract: This study was conducted between April and June 2008 in the labour ward of Elfasher Hospital in western Sudan to investigate the prevalence of and risk factors for low birthweight (LBW; <2500g). Among 430 singleton births, 64 (14.9%) of the neonates had LBW. Although maternal sociodemographic characteristics and anthropometric measurements were not associated with LBW, maternal anaemia was the main risk factor for LBW (odds ratio: 5.1, 95% CI 1.7-15.2; P=0.003). Thus more attention to maternal nutrition and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 9 publications
10
38
5
2
Order By: Relevance
“…In Sudan-which is the biggest country in Africa-we reported that pregnant women of the eastern region are more susceptible to anaemia irrespective of their age or parity [3] and anaemia associated with poor maternal and perinatal outcomes [12,13].…”
Section: Introductionmentioning
confidence: 97%
“…In Sudan-which is the biggest country in Africa-we reported that pregnant women of the eastern region are more susceptible to anaemia irrespective of their age or parity [3] and anaemia associated with poor maternal and perinatal outcomes [12,13].…”
Section: Introductionmentioning
confidence: 97%
“…Fewer mothers in the LBW group than the mothers of NBW infants were classified as underweight (7 Table 3). In both LBW and NBW groups some mothers had hyperemesis gravidarum in first trimester of pregnancy, so their weight loss was more than weight gain during pregnancy.…”
Section: Mothers' Anthropometric Characteristicsmentioning
confidence: 99%
“…As the incidence of LBW is one of the best indicators for evaluating the success of maternal and child programmes [4,5] LBW has featured in the health targets of a number of international organizations. Reducing the incidence of LBW babies by at least one-third by 2010 was one of the goals of WHO [6] and a United Nations resolution in 2000 [7]. Since 38.0% of child mortality occurs during the first month of birth and is directly related to birth weight, LBW is also an important indicator for monitoring the achievement of Millennium Developmental Goal 4, to reduce child mortality by two-thirds by 2015 [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Low birth weight (LBW) and preterm delivery have been persistently linked to anemia in pregnancy. [2,6] The main causes of anemia in developing countries include inadequate intake and poor absorption of iron, malaria, hookworm infestation, diarrhea, HIV/AIDS and other infections, genetic disorders (e.g., sickle cell and thalassemia), blood loss during labor and delivery, heavy menstrual blood flow, and closely spaced pregnancies. [7] In view of the above, the present study was carried out find out the prevalence of anemia among pregnant women and its impact on perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%